KRITIK TERHADAP QIRA’AH AL-QUR’AN PERSPEKTIF ORIENTALIS - Wahyudi, Rudi (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
On the orientalist perspective such as Mingana, Nӧldeke, dan Goldziher many qiraah types that exists today is a sign of many contradiction in the Quran.  It means the authenticity of the Quran, today, is very doubtful.  On their perspective, the cause of the qiraah differencies is simplicity of Arabic writing which its letters, at that time, is empty from diacritics and letter marks.  It makes everyone read Quran according to their own perceptions.  This orientalist perspective is clearly contrary to the Muslim perspective, where the writings is not the only source of Quran recitation.  There is another source of recitation which is more important than the writings, riwāyah.  Riwayah is a way to convey a news to the other from the memory, not from the text.  For the illiterate people, to memorize every important things and its transmission (sanad) is more important than to write it down.  The orientalists, in many cases, failed to understand the culture because they stands besides the people as observer not participant.  They uses their own glasess to capture the phenomena ahead.  This such a perspective would produce a lot of distortion and a-history’s view.